Crystallization and Resolution of cis‐Permethric Acid with Carbon Dioxide Antisolvent. Issue 8 (9th July 2014) - Bánsághi, György; Lőrincz, László; Szilágyi, Imre Miklós; Madarász, János; Székely, Edit; Qu, Haiyan; Rantanen, Jukka; Ulrich, Joachim
Abstract Crystallization and resolution of cis‐permethric acid (cPA) with (1R)‐1‐phenylethanamine (PhEA) as a resolving agent was investigated by means of gas antisolvent (GAS) and supercritical antisolvent (SAS) methods. A significant pressure effect on both the yields and diastereomeric excesses of the crystallized cPA‐PhEA salts was observed in a defined pressure range. The pressure effect was found to be related to the structure and dissociation of the salts. Both methods yielded diastereomeric salts with excellent diastereoselectivity, compared to data reported in literature, and a fibrous structure of uniform fiber diameter.